Study on Climate Change Impacts on Restionaceae Species in Jonkershoek, South Africa - (:unkn) unknown (My University, 2021)
The Restionaceae species of the Fynbos biome is part of the Cape Floristic Region (CFR) that is threatened by urbanization, agricultural expansion, groundwater extraction, and climate change. Therefore, it is necessary to assess and monitor the Restionaceae species under the impact of climate change. South Africa is a semi-arid environment, and hydrological factors are the main variables in the determination of species niches. This study investigates the microclimate at Jonkershoek, and examines the impact of climate change to the plant species distribution, thus creating shifts in the hydrological niche. This study generates its own unique microclimate hydrological datasets for modelling species niche. The Restionaceae species and their hydrological niche at the Jonkershoek study area are assessed under future climate change scenario, at a microclimatic level. It provided evidence regarding the importance of the study to understanding the climate change impacts on hydrological niche and on species richness. As the CFR has been widely used as a test case for modelling climate change impacts on biodiversity at biome and species level, many studies have projected range contractions and species losses. This study should be further explored as representative of climate change impacts on the hydrological niche of the Restionaceae species in the long term observations.
Keywords: African Research